Improper use of spinetoram on tea plants can inhibit the predation ability of Arma chinensis - Chen, Qiang; Chen, Hongyun; Qu, Hao; Luo, Ziwen; Long, Lixue; Long, Yaqin; Chen, Linbo (Ecotoxicology and environmental safety, 2025)
The application of pesticides is indispensable in agricultural production and mitigate the negative impact is crucial nowadays. The Agriophara rhombata is a major pest on tea trees and the Arma chinensis is a beneficial insect and its natural enemy in field production. Application of the Spinetoram to control A. rhombata has a significant impact on the A. chinensis population. To explore the effect of the spinetoram under A. chinensis were realized approaches such as virulence studies as well as the construction of a predatory functional response model, and the determination of detoxification enzymes. It was discovered that the predatory functional response model of 3rd-5th instar nymphs and male and female adults of the A. chinensis to 3rd-4th instar larvae of A. rhombata was Holling II functional response. With the increase in the spinetoram concentration, the handling time of the A. chinensis augmented, while the instantaneous attack rate, predation capacity, and maximum prey consumed daily declined. The spinetoram affected the control ability of the A. chinensis as well as the search ability of nymphs and adults under high doses of the spinetoram. The activities of glutathione S-transferase (GST) and carboxylesterase (CarE) in the A. chinensis increased with the increase in instar then, decreased with the increase in the spinetoram concentration. It is speculated that GST and CarE are involved in the detoxification of spinetoram in A. chinensis. When releasing the A. chinensis into the field we must avoid concurrent application with pesticides and the number of A. chinensis should be reasonably determined based on the area and prey density, to reduce interference among natural enemies. •The lethal concentration of spinetoram for Arma chinensis increases with instar.•Arma chinensis predation on Agriophara rhombata follows the Holling II model.•GST and CarE measurements suggest involvement in spinetoram metabolism.